A Mini-Review of the Role of Glutamate Transporter in Drug Addiction - Wang, Wenjun; Zeng, Fancai; Hu, Yingying; Li, Xiang (Frontiers in Neurology, 2019)
Goals: The development of new treatment for drug abuse requires identification of targetable molecular mechanisms. The pathology of glutamate neurotransmission system in the brain reward circuit is related to the relapse of multiple drugs. Glutamate transporter regulates glutamate signaling by removing excess glutamate from the synapse. And the mechanisms between glutamate transporter and drug addiction are still unclear. Methods: A systematic review of the literature searched in Pubmed and reporting drug addiction in relation to glutamate transporter. Studies were screened by title, abstract, and full text. Results: This review is to highlight the effects of drug addiction on glutamate transporter and glutamate uptake, and targeting glutamate transporter as an addictive drug addiction treatment. We focus on the roles of glutamate transporter in different brain regions in drug addiction. More importantly, we suggest the functional roles of glutamate transporter may prove beneficial in the treatment of drug addiction. Conclusion: Overall, understanding how glutamate transporter impacts central nervous system may provide a new insight for treatment of drug addiction.